La contaminación ambiental urbana y su incidencia al medio ambiente lesionan la tutela constitucional - Ormaza Palma, Carlos Cesar (2016)
The subject of this research is urban environmental pollution and its impact on the environment harms the constitutional protection, covering soil contamination by waste, toxic waste, chemicals, and industrial waste, this produces a physical imbalance, chemical and biological which affects plants, animals and cause serious diseases in humans. Among those hazardous wastes waste, both biological origin which have not lie. This waste is identified by forming a potential risk to the environment, which are not to be treated like any other here are some examples: corrosives, acids, radioactive materials and infectious medical remains. These materials should receive a singular treatment and those who generate them must be careful with them singular. It is considered that the beneficiaries of this research are all people using the natural resource of Ecuador. Similarly, the implementation of the proposal which is determined at the end of Legal project will have a social significance, water rights be guaranteed, avoiding contamination in terms of feasibility, the research was supported by the State Technical University Quevedo, teacher of the Faculty of Law immersed in the problem, the cooperation of our specialty partners also counted with material, financial and self-management resources with which it was possible to conduct the investigation.